On thermodynamics of methane+carbonaceous materials adsorption - Rahman, Kazi Afzalur (2013)
This study presents the theoretical frameworks for the thermodynamic quantities namely the heat of adsorption, specific heat capacity, entropy, and enthalpy for the adsorption of methane onto various carbonaceous materials. The proposed theoretical frameworks are developed from the rigor of thermodynamic property surfaces of a single component adsorbate–adsorbent system and by incorporating the micropore filling theory approach, where the effect of adsorbed phase volume is considered. The abovementioned thermodynamic properties are quantitatively evaluated from the experimental uptake data for methane adsorption onto activated carbons such as Maxsorb III at temperatures ranging from 120 to 350 K and pressures up to 25 bar. Employing the proposed thermodynamic approaches, this paper shows the thermodynamic maps of the charge and discharge processes of adsorbed natural gas (ANG) storage system for understanding the behaviors of natural gas in ANG vessel.